Clinical symptoms in fibromyalgia are associated to catechol-O-methyltransferase (COMT) gene Val158Met polymorphism. (October 2014) - Inanir, Ahmet; Karakus, Nevin; Ates, Omer; Sezer, Saime; Bozkurt, Nihan; Inanir, Sema; Yigit, Serbulent
Abstract 1. Fibromyalgia syndrome (FMS) is a common chronic widespread pain syndrome mainly affecting women. The aim of this study was to explore the frequency and clinical significance of catechol-O-methyltransferase (COMT) gene Val158Met polymorphism in a large cohort of Turkish patients with FMS. 2. The study included 379 FMS patients and 290 controls. Genomic DNA was isolated and genotyped using polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analyses. 3. The genotype frequencies of Val158Met polymorphism showed a small difference between FMS patients and healthy controls (p = 0.047), however, the Met/Met genotype was significantly higher in FMS patients than healthy controls (p = 0.016). No difference was observed for allele frequencies between two groups. Stratification analysis according to clinical features for this disease reveals that weight, FMS Impact Questionnaire score, algometry and Raynaud's syndrome, were detected to have statistically significant associations with Val158Met polymorphism (p = 0.037, p = 0.042, p = 0.039 and p = 0.033, respectively). Pain sensitivity, measured by algometry, was statistically higher in patients with Met/Met genotype than the patients with Val/Val and Val/Met genotypes (p = 0.017). 4. The results of this study suggested that COMT gene Val158Met polymorphism is positively associated with FMS and play a relevant role in the clinical symptoms of the disease.